2009
DOI: 10.1016/j.jep.2009.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Davilla elliptica and Davilla nitida: Gastroprotective, anti-inflammatory immunomodulatory and anti-Helicobacter pylori action

Abstract: The phytochemical investigation showed that both extracts possess phenolic acid derivatives, acylglycoflavonoids and condensed tannins with evident quantitative variations that probably influenced the pharmacological differences between extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
0
27
0
3
Order By: Relevance
“…It is an important enzyme for the gastric mucosa because it, in cicatrisation process, induces angiogenesis, cell proliferation and cytoprotection, related to the production of prostaglandins that stimulates mucus and bicarbonate production (Brzozowski et al, 2000). Kushima et al (2009) studying Flavonoid fraction from Davilla elliptica observed that the number of COX-2 marked cells lowers dose-dependently, which confirms flavonoids antiinflammatory effect by inhibition of COX-2 (Robak and Gryglewski, 1996). In the study of the Tannins fraction from Davilla elliptica by Kushima et al (2009), COX-2 expression tended to rise also dose dependently, although it was not related to the mechanism of action of this plant.…”
Section: Ethanol-induced Ulcersmentioning
confidence: 76%
“…It is an important enzyme for the gastric mucosa because it, in cicatrisation process, induces angiogenesis, cell proliferation and cytoprotection, related to the production of prostaglandins that stimulates mucus and bicarbonate production (Brzozowski et al, 2000). Kushima et al (2009) studying Flavonoid fraction from Davilla elliptica observed that the number of COX-2 marked cells lowers dose-dependently, which confirms flavonoids antiinflammatory effect by inhibition of COX-2 (Robak and Gryglewski, 1996). In the study of the Tannins fraction from Davilla elliptica by Kushima et al (2009), COX-2 expression tended to rise also dose dependently, although it was not related to the mechanism of action of this plant.…”
Section: Ethanol-induced Ulcersmentioning
confidence: 76%
“…Diversos estudos sobre atividade biológica de plantas medicinais contendo taninos e flavonoides evidenciaram dentre outras ações a cura de feridas, atividades antiinflamatória, antiulcerogênica gástrica e antioxidante (Kushima et al, 2009;Moleiro et al, 2009). Taninos podem interagir com as proteínas do muco, melhorando seu efeito citoprotetor pela formação de um revestimento proteico na mucosa gastrintestinal (Okuda, 2005;Moleiro et al, 2009).…”
Section: Resultsunclassified
“…Besides its H. pylori bactericidal effect, Davilla elliptica also enhances NO, H 2 O 2 , TNFproduction and GSH bioavailability. These activities are related to its phytochemical constituents acylglycoflavonoids, phenolic acid derivatives and tannins (74). Also Brazilian medicinal plant methanolic extracts have an anti-H. pylori effect and protect the gastric mucosa by increasing PGE2, antisecretory and gastroprotective properties (75) The gastroprotection of Vochysia tucanorum Mart.…”
Section: Herbs Combined Activitiesmentioning
confidence: 99%
“…In disparity, many spices and plant extracts, in commonly used dose, up to 500mg/kg body weight have not exhibited adverse effect. These include cardamom (62,68), black pepper (66), clove (67), caraway (69), saffron (70),coriander(71), peppermint (72), anise (73), davilla elliptica and nitida (74) ,Brazilian medical plants (75) and Alchornea triplinervia (76) and Hyptis spicigera Lam (86). Even in pregnancy, ginger, peppermint, and Cannabis have been used to treat nausea were effective and lack clinical evidence of harm (165).…”
Section: Wwwintechopencommentioning
confidence: 99%